Culture and social transformations in reform era China - Cao, Tian Yu, 1941-; Zhong, Xueping, 1956-; Liao, Kebin, 1961- (Ideas, history, and modern China, 2010)
Leading scholars examine the interplay between the ideological reorientation and radical social changes in contemporary China in terms of the interpretation, appropriation and mobilization of three major cultural resources (traditional, May Fourth, and socialist) by various social groups.